A Finnish adaptation of the emotion regulation questionnaire (ERQ) and the difficulties in emotion regulation scale (DERS-16). Issue 4 (2nd October 2018) - Westerlund, Minja; Santtila, Pekka
Abstract: The emotion regulation questionnaire (ERQ) and a short form of the difficulties in emotion regulation scale (DERS-16) were psychometrically evaluated in a Finnish, population-based sample ( n  = 409 for ERQ, n  = 400 for DERS-16). The original two-factor structure of the ERQ was supported, after eliminating one item due to low loadings. A five-factor structure was supported for DERS-16, after dropping two items due to cross loadings. Both scales showed adequate internal consistencies. Women had a significantly stronger tendency to use reappraisal strategies than men did, and men used suppression significantly more than women. There were no gender differences on DERS-16. Age affected both ERQ and DERS-16. We conclude that both scales are psychometrically adequate for use in the Finnish population even though validation studies are needed.